2021
DOI: 10.1371/journal.pone.0254197
|View full text |Cite
|
Sign up to set email alerts
|

Electronic media use and symptoms of depression among adolescents in Norway

Abstract: Background The purpose of this study was to examine the association between electronic media use, including use of social media and gaming, and symptoms of depression, and whether gender or having friends moderated these associations. Methods This study was based on self-reported cross-sectional data from the Ungdata survey, conducted in 2018 by the Norwegian Social Research (NOVA) Institute in cooperation with seven regional drug and alcohol competence centres. The target group comprised 12,353 15–16 years … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Among the students, more time spent using social media was associated with poorer mental health and well-being and more emotional loneliness. While these findings are in line with those of several studies conducted during and before the COVID-19 pandemic [ 24 , 47 , 48 , 49 , 50 , 51 ], we note that the strength of the associations detected within the student sample appears to be more substantive than the comparable associations found in the general populations studied e.g., [ 20 , 52 ]. Social media is by far more widely adopted among adolescents and young adults, compared to those in the older age groups [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Among the students, more time spent using social media was associated with poorer mental health and well-being and more emotional loneliness. While these findings are in line with those of several studies conducted during and before the COVID-19 pandemic [ 24 , 47 , 48 , 49 , 50 , 51 ], we note that the strength of the associations detected within the student sample appears to be more substantive than the comparable associations found in the general populations studied e.g., [ 20 , 52 ]. Social media is by far more widely adopted among adolescents and young adults, compared to those in the older age groups [ 53 ].…”
Section: Discussionsupporting
confidence: 92%
“…Current evidence on youth gaming is predominantly based on gaming consoles, and not gaming on smartphones. A study in Norway found that gaming use was associated with higher odds of symptoms of depression, although they used a 3 h cut-off compared with our 2 h cut-off and they did not investigate weekday versus weekend day differences [40]. On the other hand, similar to our findings, a meta-analysis (on all screen time) and a recent longitudinal study from the UK (on gaming specifically) reported that more frequent video gaming was associated with fewer depressive symptoms [41,42].…”
Section: Discussionmentioning
confidence: 97%
“…T.D. Ray [47] reported that adolescents experiencing social comparison and cyberbullying during a developmental Eight articles reported that females who use social media showed higher depression symptoms than males who did [16,18,28,29,40,43,50,52]. Maheux et al [43] explained in their paper that females have reported a higher overall score on the Appearance-Related Social Media Consciousness scale (ASMC), which explains why females might be more affected by social media use which, therefore, increases their depressive symptoms.…”
Section: Resultsmentioning
confidence: 99%